Enhanced Long‐Term Cathode Stability by Tuning Interfacial Nanocomposite for Intermediate Temperature Solid Oxide Fuel Cells. Issue 14 (30th March 2022) - Hu, Dingyue; Dawson, Karl; Zanella, Marco; Manning, Troy D.; Daniels, Luke M.; Browning, Nigel D.; Mehdi, B. Layla; Xu, Yaobin; Amari, Houari; Shin, J. Felix; Pitcher, Michael J.; Chen, Ruiyong; et al.
Abstract: Performance durability is one of the essential requirements for solid oxide fuel cell materials operating in the intermediate temperature range (500–700 °C). The trade‐off between desirable catalytic activity and long‐term stability challenges the development and commercialization of electrode materials. Here an oxygen cathode material, Ba0.5 Sr0.5 (Co0.7 Fe0.3 )0.69− x Mg x W0.31 O3− δ (BSCFW‐ x Mg), that exhibits excellent electrocatalytic performance through the addition of an optimized amount of Mg to the self‐assembled nanocomposite Ba0.5 Sr0.5 (Co0.7 Fe0.3 )0.69 W0.31 O3− δ (BSCFW) by simple solid‐state reaction is reported. Distinct from the bulk and surface approaches to introduce vacancies and defects in materials design, here the Mg 2+ ions concentrate at the single perovskite/double perovskite interface of BSCFW with dislocations and Mg 2+ ‐rich nanolayers, resulting in stressed and compositionally inhomogeneous interface regions. The interfacial chemistry within these nanocomposites provides an additional degree of freedom to enable performance optimization over single phase materials and promotes the durability of alkaline‐earth based fuel cell materials. Abstract : The single perovskite (SP) and double perovskite (DP) coexisting solid oxide fuel cell cathode material Ba0.5 Sr0.5 (Co0.7 Fe0.3 )0.64 Mg0.05 W0.31 O3− δ is synthesized by a simple solid‐state reaction method and displays remarkable long‐term stability and catalytic performance attributed to the novel Mg‐rich and strained SP/DP interfaces. This modified interfacial nanocomposite by self‐assembly represents an alternative path to analogy with surface deposition techniques.